(untitled) (Commonwealth Journal of Local Governance, 2020)
In 2013 and 2019, the local government legislation of the province of Punjab in Pakistan saw two rounds of major changes – each of which led to a new local government Act being passed. In 2013 the changes were driven by constitutional and judicial requirements and in 2019 by the political will of Pakistan’s new coalition government. This article analyses and compares the functional assignment (FA) architecture of the two Acts against a set of parameters. The study finds that marginal improvements to the FA architecture introduced by the 2019 Act are offset by continuing inconsistencies and lack of clarity over ‘who does what’ in the functions assigned to local governments. The authors suggest that improving the functionality of local governments requires full implementation of the design features of the new system, including institutional strengthening of provincial-level entities which regulate and oversee the local government system.